2009
DOI: 10.1038/labinvest.2008.157
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of interleukin-6 and endoplasmic reticulum stress inducers on the high level of ABCG2 expression in plasma cells

Abstract: ABCG2 is a transporter preferentially expressed in a primitive subpopulation of cells and recently reported as a surviving factor for trophoblasts. To date, manner of ABCG2 expression in lymphoid tissues is not known. Immunohistochemically, strong ABCG2 expression was found in a small proportion of plasma cells mainly located in the interfollicular space of lymphoid tissues. The number of ABCG2-high plasma cells increased in interleukin-6-(IL-6) rich lesions, such as Castleman's disease of plasma cell type. Pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…This could be of potential interest given the recent studies showing that operationally tolerant patients display a particular B cell profile highlighting a possible abnormal B cell differentiation process in these patients [11], [12], [27], [28]. A recent paper have reported that the STAT3/IL-6 pathway, that has also been shown to be involved in ER stress [29], [30], is activated neither in operationally tolerant patients nor in rejecting patients [31]. These results that do not confort our hypothesis may be due to the fact that the STAT3/IL-6 pathway is not the only signaling pathway reflecting UPR activity, and the absence of its activity in operationally tolerant or rejecting patients may not preclude the absence of UPR activity in the PBMCs of these patients.…”
Section: Discussionmentioning
confidence: 97%
“…This could be of potential interest given the recent studies showing that operationally tolerant patients display a particular B cell profile highlighting a possible abnormal B cell differentiation process in these patients [11], [12], [27], [28]. A recent paper have reported that the STAT3/IL-6 pathway, that has also been shown to be involved in ER stress [29], [30], is activated neither in operationally tolerant patients nor in rejecting patients [31]. These results that do not confort our hypothesis may be due to the fact that the STAT3/IL-6 pathway is not the only signaling pathway reflecting UPR activity, and the absence of its activity in operationally tolerant or rejecting patients may not preclude the absence of UPR activity in the PBMCs of these patients.…”
Section: Discussionmentioning
confidence: 97%
“…The nature of secreted microglia factors responsible for inducing ABCG2 expression in HBEC is presently unclear, although preliminary evidence suggested that cytokines IL-1 and TNFα are not important effectors. Recent studies reporting that IL-6 or endoplasmic reticulum (ER) stress induce ABCG2 expression in plasma cells (Nakamichi et al, 2009) and that IL-6 is up-regulated in HBEC treated with Aβ 1-40 peptides, as well as in AD and AD/CAA brains (Vukic et al, 2008), suggest IL-6 as a potential mediator of ABCG2 up-regulation in AD. Since it is difficult to recreate in vivo chronic exposure of the multicellular neurovascular unit to Aβ peptides, hypoxia and inflammatory microenvironment in cell culture models, we cannot rule out the possibility that the combination of these factors might be responsible for stimulation of vascular ABCG2 expression in AD.…”
Section: Discussionmentioning
confidence: 99%
“…Estradiol (E2) activates or represses BCRP expression by binding of estrogen receptor α (ERα) to an estrogen response element (ERE) [65]. Interleukin-6 as well as endoplasmic reticulum stress stimulate BCRP expression in plasma cells by binding of XBP-1 and/or HIF-1α to the BCRP HRE [66]. Also, progesterone receptor isoform B (PRB) but not PRA binding to the progesterone response element (PRE), overlapping with the ERE site, enhances BCRP expression [67, 68].…”
Section: Section 2 Background: Bcrp In Cancer Drug Resistancementioning
confidence: 99%